1993
DOI: 10.1016/0165-1218(93)90048-i
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle dependent micronucleus formation and mitotic disturbances induced by 5-azacytidine in mammalian cells

Abstract: Summary 5-Azacytidine was originally developed to treat human myelogenous leukemia. However, interest in this compound has expanded because of reports of its ability to affect cell differentiation and to alter eukaryotic gene expression. In an ongoing attempt to understand the biochemical effects of this compound, we examined the effects of 5-azacytidine on mitosis and on micronucleus formation in mammalian cells. In L5178Y mouse cells, 5-azacytidine induced micronuclei at concentrations at which we and others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, the in vitro micronucleus test is also suitable for the evaluation of genotoxicity (1)(2)(3)(4)(5)(6)(7) and is applied to human biomonitoring (8,9). Since radiationinduced micronuclei show a clear dependence on radiation dose and its quality (10)(11)(12)(13)(14), the micronucleus assay can be applied as a biological dosimeter.…”
Section: Introductionmentioning
confidence: 99%
“…However, the in vitro micronucleus test is also suitable for the evaluation of genotoxicity (1)(2)(3)(4)(5)(6)(7) and is applied to human biomonitoring (8,9). Since radiationinduced micronuclei show a clear dependence on radiation dose and its quality (10)(11)(12)(13)(14), the micronucleus assay can be applied as a biological dosimeter.…”
Section: Introductionmentioning
confidence: 99%
“…However, DES as well as 5-azacytidine induced DNA hypomethylation in SHE cells [10]. In addition, 5-azacytidine has been shown to perturb G2 phase transit [11] and to induce micronuclei in SHE cells [12,13]. Cytogenetic analysis revealed that the ma jority of micronuclei induced by 5-azacytidine treatment did not contain whole chromosomes, but chromatin frag ments [12].…”
Section: Resultsmentioning
confidence: 99%
“…For example, alkylation of the nucleotide pool may lead to aneuploidy through induction of nucleotide modifications of the centromeric region and, as a consequence, changes in the functional state of the kinetochore [75]. Aneuploidy may also be a consequence of interchromosome translocation [77]. It has been discovered that accelerated decondensation of the chromatin of individual chromosomes in connection with a disturbance in the kinetochore organization is apparently also accompanied by aneuploidy [76].…”
Section: Aneuploidymentioning
confidence: 99%